Cancer and Thrombosis: The Platelet Perspective - Meikle, Claire K. S.; Kelly, Clare A.; Garg, Priyanka; Wuescher, Leah M.; Ali, Ramadan A.; Worth, Randall G. (Frontiers in Cell and Developmental Biology, 2017)
Platelets are critical to hemostatic and immunological function, and are key players in cancer progression, metastasis, and cancer-related thrombosis. Platelets interact with immune cells to stimulate anti-tumor responses and can be activated by immune cells and tumor cells. Platelet activation can lead to complex interactions between platelets and tumor cells. Platelets facilitate cancer progression and metastasis by: 1) forming aggregates with tumor cells; 2) inducing tumor growth, epithelial-mesenchymal transition, and invasion; 3) shielding circulating tumor cells from immune surveillance and killing; 4) facilitating tethering and arrest of circulating tumor cells; and 5) promoting angiogenesis and tumor cell establishment at distant sites. Tumor cell-activated platelets also predispose cancer patients to thrombotic events. Tumor cells and tumor-derived microparticles lead to thrombosis by secreting procoagulant factors, resulting in platelet activation and clotting. Platelets play a critical role in cancer progression and thrombosis, and markers of platelet-tumor cell interaction are candidates as biomarkers for cancer progression and thrombosis risk.